Korelacje porządku rang Charlesa Spearmana pomiędzy zmianami postawy w płaszczyźnie strzałkowej a reakcjami posturalnymi u dziewcząt w wieku 12-15 lat = Correlations of Charles Spearman rank order between changes of posture in a sagittal plane and postural reactions in girls aged 12-15 years - Wilczyński, Jacek; Karolak, Przemysław; Paprocki, Michał Jerzy; Rychter, Paweł; Wilczyński, Igor (Journal of Education, Health and Sport, 2016)
Wilczyński Jacek, Karolak Przemysław, Paprocki Michał, Rychter Paweł, Wilczyński Igor. Korelacje porządku rang Charlesa Spearmana pomiędzy zmianami postawy w płaszczyźnie strzałkowej a reakcjami posturalnymi u dziewcząt w wieku 12-15 lat = Correlations of Charles Spearman rank order between changes of posture in a sagittal plane and postural reactions in girls aged 12-15 years. Journal of Education, Health and Sport. 2016;6(5):38-54. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.51100 http://ojs.ukw.edu.pl/index.php/johs/article/view/3509 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.04.2016. Revised 25.04.2016. Accepted: 05.05.2016. KORELACJE PORZĄDKU RANG CHARLESA SPEARMANA POMIĘDZY ZMIANAMI POSTAWY W PŁASZCZYŹNIE STRZAŁKOWEJ A REAKCJAMI POSTURALNYMI U DZIEWCZĄT W WIEKU 12-15 LAT CORRELATIONS OF CHARLES SPEARMAN RANK ORDER BETWEEN CHANGES OF POSTURE IN A SAGITTAL PLANE AND POSTURAL REACTIONS IN GIRLS AGED 12-15 YEARS Jacek Wilczyński, Przemysław Karolak, Michał Paprocki, Paweł Rychter, Igor Wilczyński Instytut Fizjoterapii, Wydział Lekarski i Nauk o Zdrowiu, UJK w Kielcach dr hab. n. o k. f. Jacek Wilczyński, mgr Przemysław Karolak, mgr Michał Paprocki, mgr Paweł Rychter, licencjat Igor Wilczyński Instytut Fizjoterapii, Wydział Lekarski i Nauk o Zdrowiu, UJK w Kielcach Słowa kluczowe: korelacje porządku rang Charlesa Spearmana, zmiany postawy w płaszczyźnie strzałkowej, reakcje posturalne. Key words: correlations of Charles Spearman rank, changes of posture in a sagittal plane, postural reactions. Streszczenie Celem pracy była analiza korelacji porządku rang Spearmana pomiędzy zmianami postawy w płaszczyźnie strzałkowej a reakcjami posturalnymi u dziewcząt w wieku 12-15 lat. W badaniach brało udział 247 dziewcząt w wieku 12-15 lat ze Szkoły Podstawowej Nr 13 i Gimnazjum Nr 4 w Starachowicach. Badania wykonano w listopadzie 2005 roku. W badaniach postawy zastosowano technikę fotogrametrii przestrzennej wykorzystującą efekt mory projekcyjnej. W badaniach reakcji równoważnych zastosowano platformę Cosmogamma by Emildue R 50300. Wykonywano standardowy test Romberga w staniu swobodnym. Do analizy statystycznej zastosowano średnią arytmetyczną (x) i odchylenie standardowe (s). Rozkłady zmiennych opisujących postawę analizowano testem Liliefors. Reakcje posturalne zweryfikowano pod względem normalności rozkładu testem Kołmogorowa-Smirnowa. W przypadku, gdy rozkład próby różnił się istotnie od normalnego dla wyznaczenia współzależności dwóch cech zastosowano nieparametryczny test korelacji Spearmana. W grupie dziewcząt dominowały korelacje wprost proporcjonalne, których było siedem: DELTA/SPOY (OE), DKP/GP (OE), DKP/DS (OE), DKP/PB (OE), GLL/SPOY (OE), DLL/SPOY (CE), DKP/PP (OE). Korelacje odwrotnie proporcjonalne wystąpiły w czterech przypadkach: RLL/PP (CE), DCK WZR/SPOX (OE), DLL/PP (CE), KLL/SPOY (OE). Korelacje istotne statystycznie częściej występowały, kiedy test Romberga odbywał się z oczami otwartymi (OE): DELTA/SPOY (OE), DKP/GP (OE), DKP/DS (OE), DKP/PB (OE), GLL/SPOY (OE), DKP/PP (OE), DCK WZR/SPOX (OE) KLL/SPOY (OE). Wśród korelacji z oczami otwartymi (OE) było sześć wprost proporcjonalnych: DELTA/SPOY (OE), DKP/GP (OE), DKP/DS (OE), DKP/PB (OE), GLL/SPOY (OE), DKP/PP (OE) i tylko dwie ujemne: DCK WZR/SPOX (OE), KLL/SPOY (OE). W teście Romberga z oczami zamkniętymi (CE) wystąpiła jedna istotna korelacja dodatnia: DLL/SPOY (CE) i dwie korelacje ujemne: RLL/PP (CE), DLL/PP (CE). Summary The aim of this study was to analyze the correlation of the Spearman rank order between changes of posture in the sagittal plane and postural reactions in girls aged 12-15 years. The studies included 247 girls aged 12-15 years from the Primary School No. 13 and Grammar School No. 4 in Starachowice. The study was performed in November 2005. The research approach used photogrammetry technique that uses spatial projection moiré effect. The study of balance reaction sense study used the Cosmogamma platform by Emildue R 50300. Romberg test was performed in a standard free standing. For statistical analysis, the arithmetic mean (x) and standard deviation (s) were used. The distributions of variables describing the posture were analyzed by Liliefors test. Postural reactions were verified in terms of distribution normality with Kolmogorov-Smirnov test. If the distribution of the sample differed significantly from normal, for determining the correlation between two characteristics, nonparametric Spearman correlation test was used. In the group of girls dominated proportional correlations, in the number of seven: DELTA/SPOY (OE), DKP/GP (OE), DKP/DS (OE), DKP/PB (OE), GLL/SPOY (OE), DLL/SPOY (CE), DKP/PP (OE). Correlates inversely proportional occurred in four cases: RLL/PP (CE), DCK WZR/SPOX (OE), DLL/PP (CE), KLL/SPOY (OE). Statistically significant correlations were more frequent when the Romberg test was conducted with eyes open (EO): DELTA/SPOY (OE), DKP/GP (OE), DKP/DS (OE), DKP/PB (OE), GLL/SPOY (OE), DKP/PP (OE), DCK WZR/SPOX (OE) KLL/SPOY (OE). Among the correlation with eyes open (EO) was six directly proportional: DELTA/SPOY (OE), DKP/GP (OE), DKP/DS (OE), DKP/PB (OE), GLL/SPOY (OE), DKP/PP (OE) and only two negative: DCK WZR/SPOX (OE), KLL/SPOY (OE). In the Romberg test with eyes closed (CE) there was one significant positive correlation: DLL/SPOY (CE) and two negative correlations of: RLL/PP (Z), DLL/PP (CE).